System identification applied to long span cable supported bridges using seismic records. - Siringoringo, Dionysius M. (Earthquake engineering & structural dynamics.)
This paper presents the application of system identification (SI) to long span cable supported bridges using seismic records. The SI method is based on the System Realization using Information Matrix (SRIM) that utilizes correlations between base motions and bridge accelerations to identify coefficient matrices of a state space model. Numerical simulation using a benchmark cable stayed bridge demonstrate the advantages of this method in dealing with multiple input multiple output (MIMO) data from relatively input inclusion, and the types of input with respect to identification results are also investigated. The method is applied to identify modal parameters of the Yokohama Bay Bridge, Rainbow Bridge and Tsurumi Fairway Bridge using the records from the 2004 Chuetsu-Niigata earthquake. Comparison of modal parameters with the results of ambient vibration tests, forced vibration tests, and analytical models are presented together with discussions regarding the effects of earthquake excitation amplitude on global and local structural modes.